Analysis of geometric factors for an X-ray fluorescence analyzer designed via the Monte Carlo method - Liu Hefan; Tian Hong; Zhou Laidong; Zhou Zihang; Huang Fengxia; Lu Chengwei; Zeng Guoqiang; Hu Xiang (MATEC Web of Conferences, 2016)
This paper presents a theoretical study on the design of an X-ray fluorescence (XRF) analyzer. The relative geometric positions of the analyzer’s source, detector and specimen are emphasized, which impacts the analyte’s characteristic X-ray fluorescence counts. The theoretical formula for the X-ray fluorescence intensity was derived. The geometric factors (angle and distance) were simulated using Monte Carlo Neutron-Particle Transport Code MCNP5. The Cu’s X-ray characteristic peak counts were calculated. These Monte Carlo model calculations analyzed two types of geometry changes. The best geometric positions for the XRF analyzer had the incident angle for the excitation source (β) equivalent to the exit angle for the specimen’s characteristic X-ray (β). The maximal characteristic X-ray peak counts were obtained when α and β were orthogonal, and the minimum counts were obtained when parallel. To increase the fluorescence counts, the source and detector should be set as close to the specimen as possible. This method and these conclusions can provide technical guidance for designing XRF analyzers.